Salman Rushdie’s ‘Epico-Mythico-Tragico-Comico-Super-Sexy-High-Masala-Art,’ or Considerations on Undisciplining Boundaries - Mendes, Ana Cristina (2012)
In Salman Rushdie’s work, pictures are invested with the power to manipulate the plotline, to stipulate actions from the characters, to have sway over them, enchant or even haunt them. References to the visual – notably, film, TV, comic books, photography, and painting – crowd Rushdie’s writing. Several of his characters are directly connected to the realm of visuality and portrayed as availing themselves of the power of visual representation or as submitting to the pictures others make of them. In his writing, with its wealth of pictures, the visual is hence a site where meaning is constructed and struggles over representation are staged. In attempting to shed light on a largely unexplored, even if central, dimension of the narrative project of a major contemporary author – the extensive interplay between what might be termed, for the sake of brevity, ‘the visible’ and ‘the readable’ –, this collection focuses on ‘pictures’ instead of ‘images’ to encapsulate the complex ways in which the visual is here transcribed into the printed word, and the different levels at which that occurs. This means exploring not only the visual quality or effect that Rushdie strives for in his texts, but also the influence of the visual on the author and the multifarious ways the visual is apprehended and represented in the body of his work.